EFFECTIVENESS OF THE DIGITAL INTERACTIVE CASE-BASED LEARNING (DICL) METHOD IN MEDICAL EDUCATION IN 2015–2024 (Universal International Scientific Journal, 2026)
Digital pedagogical technologies have been widely implemented in medical education in the last decade. Digital Interactive Case-Based Learning (DICL) is an interactive teaching model based on clinical situations, which includes virtual patients and adaptive decision-making systems. The aim of this article is to analyze the impact of the DICL method on learning outcomes based on scientific studies published in 2015–2024. The results show that DICL significantly improves OSCE scores, theoretical knowledge, and clinical reasoning
Keywords: DICL; virtual patient; clinical thinking